1975
DOI: 10.1104/pp.55.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of δ-Aminolevulinic Acid in Red and Blue-Green Algae

Abstract: 5-Aminolevulinic acid was incorporated in vivo into C-phycocyanin and B-phycoerythrin in two species of the Rhodophyta (Cyanidium caldarium, Porphyridium cruentum) and three species of the Cyanophyta (Anacystis nidulans, Plectonema boryanum, Phormidium luridum). Amino acid analysis of phycocyanin-'4C from C. caldarium cells which had been incubated with 5-aminolevulinate-4-'4C showed that 84% of the radioactivity incorporated was present in the phycocyanobilin chromophore and less than 16% of the radioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…ALA is the precursor of heme in animals (17) and bacteria (10) and of chlorophyll in bacteria (5) and plants (7). Troxler and Brown (19) have shown that radioactively labeled ALA is incorporated into the chromophores (phycocyanobilin and phycoerythrobilin) of phycocyanin and phycoerythrin by red algae. Levulinic acid (LA), which is structurally similar to ALA except for the absence of the amino group, has been shown by Nandi and Shemin (15) to be a competitive inhibitor of ALA dehydratase.…”
mentioning
confidence: 99%
“…ALA is the precursor of heme in animals (17) and bacteria (10) and of chlorophyll in bacteria (5) and plants (7). Troxler and Brown (19) have shown that radioactively labeled ALA is incorporated into the chromophores (phycocyanobilin and phycoerythrobilin) of phycocyanin and phycoerythrin by red algae. Levulinic acid (LA), which is structurally similar to ALA except for the absence of the amino group, has been shown by Nandi and Shemin (15) to be a competitive inhibitor of ALA dehydratase.…”
mentioning
confidence: 99%
“…However, there is a growing body of evidence which indicates that ALA may be metabolized via nonporphyrin pathway(s) in a number of organisms (7,13,15). For example, etiolated barley leaves evolve '4C02 when fed [4-14C]ALA or [5-14C]ALA in the dark (7).…”
mentioning
confidence: 99%
“…ALA2 is the precursor of heme in animals (16) and bacteria (9); of Chl in bacteria (6) and plants (8); and of the phycobilins in red algae (19). In many organisms ALA is formed by the condensation of glycine and succinyl-CoA, catalyzed by ALA synthetase, a pyridoxal-requiring enzyme.…”
mentioning
confidence: 99%